2022
DOI: 10.21203/rs.3.rs-1520314/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinical outcomes after single induction dose of etomidate versus ketamine for emergency department sepsis intubation: a randomized controlled trial

Abstract: Background: Patients with sepsis often require emergency intubation. In emergency departments (EDs), rapid-sequence intubation with a single-dose induction agent is standard practice but the best choice of induction agent in sepsis remains controversy. High quality RCTs are needed to determine the optimal induction agents in sepsis. Methods: We conducted a randomized, controlled, single-blind trial in the ED. We included septic patients who were aged at least 18 years and required sedation for emergency intuba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…16 It has sympathomimetic properties and causes less cardiovascular depression than other induction agents, preserves protective airway reflexes, and has a potent analgesic effect. 15,17,18 While these properties seem beneficial for patients with traumatic brain injury, the use of ketamine in this patient population remains controversial. 19 In the 1970s, multiple studies found that ketamine causes an increase in intracranial pressure, [20][21][22][23] which may increase the risk of adverse outcomes in patients with traumatic brain injury.…”
Section: What This Article Tells Us That Is Newmentioning
confidence: 99%
“…16 It has sympathomimetic properties and causes less cardiovascular depression than other induction agents, preserves protective airway reflexes, and has a potent analgesic effect. 15,17,18 While these properties seem beneficial for patients with traumatic brain injury, the use of ketamine in this patient population remains controversial. 19 In the 1970s, multiple studies found that ketamine causes an increase in intracranial pressure, [20][21][22][23] which may increase the risk of adverse outcomes in patients with traumatic brain injury.…”
Section: What This Article Tells Us That Is Newmentioning
confidence: 99%